1. Editorial: CRIMEAN-CONGO HEMORRHAGIC FEVER IN THE MIDDLE EAST: HISTORY AND FACTS (Iraqi Journal of Medical Sciences, 2019)
Crimean-Congo Hemorrhagic Fever (CCHF) is the highest widespread, tick-borne viral hemorrhagic fever that affect humans. This virus is endemic in many areas in the world, such as Africa, Asia, and Europe. Nowadays, the incidence of CCHF is increasing rapidly in several countries of the middle-east, with several outbreaks and sporadic cases in human of CCHF, that are reported in several countries in this region.Keywords:CCHF, Middle east, IraqCitation: Al-Obaidi AB. Crimean-Congo hemorrhagic fever in the middle east: history and facts. Iraqi JMS. 2018; 16(2): 111-113. doi: 10.22578/IJMS.16.2.1
Keywords: CCHF; Middle east; Iraq